Awakening the metastability of an interstitial high entropy alloy via severe deformation. (15th January 2021) - Zhu, Shuya; Yan, Dingshun; Gan, Kefu; Lu, Wenjun; Li, Zhiming
Abstract: The metastability of a typical non-equiatomic FeMnCoCr high-entropy alloy (HEA) system was demonstrated to be dormant upon co-doping with C and N interstitials, i.e., displacive γ-ε phase transformation disappears during tensile deformation. Interestingly, we found in the present study that the displacive phase transformation prevails again in the C-N co-doped HEA upon severe deformation via cold-rolling. The generation of ε-phase lamellae is found to be motivated by strain localization which facilitates the formation of shear bands. Such highly concentrated strains significantly intensify the local elastic fields to neighboring γ matrix and finally eke out the driving force to overcome the interstitials-enhanced energy barrier of ε-martensite transformation. The results suggest that the suppressed phase metastability is awakened, which inspires efforts to tune the phase metastability via modifying the strain state during alloy processing and gives new insights into the development of HEAs with desirable phase stability and mechanical properties. Graphical abstract: Image, graphical abstract